Characterization of Bovine Adipose-derived Stem Cells from Two Isolation Methods - Van Hanh, Nguyen; Hong, Nguyen Thi; Thao, Vu Thi Thanh; Hanh, Le Hong; Van, Do Thanh; Chi, Ho Nguyen Quynh; Long, Le Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 41 No 4DO - 10.25073/2588-1140/vnunst.5789, 2025)
Adipose-derived stem cells (ADSCs) have great potential in regenerative medicine and tissue engineering. Especially, bovine ADSCs play an important role in the quality of artificial meat. In this study, we investigated the characterization of Zebu hybrid cattle’s ADSCs isolated by enzymatic treatment and explant culture methods from the fat pad of cattle hoof. Characterization of ADSCs was evaluated by the self-renewal and specific marker expression. The self-renewal capacity was examined by population doubling time (PDT) and growth kinetics of ADSCs. Specific markers concluded Cluster of Differentiation 73 (CD73), CD90, CD44, CD45, CD29 were analysised by polymerase chain reaction (PCR). The PDT of ADSCs from the enzymatic treatment method was significantly higher than from the explant culture method. Besides, when comparing the level of proliferation and stability of adipose stem cells, we found a difference in culture efficiency between the two methods. In addition, the expression of markers specific to adipose stem cells shows that cells from adipose tissue using two isolation methods are quite stable in morphology and the markers are maintained in expression over time. These results can have several efficient advantages in in vitro production of meat alternatives.